Estimating The Sliding Velocity Of The Rainy Lobe Using Intermediate Clast Size In Lodgement Tills - Kotrapu, Kristi (2018)
University of Minnesota M.S. thesis. August 2018. Major: Geological Sciences. Advisor: Howard Mooers. 1 computer file (PDF); v, 61 pages. Lodgement tills are important in glacier reconstruction because their properties can be used to infer parameters such as glacier sliding velocity, ice thickness, and hydrology. These tills provide important calibration parameters for mass balance studies and numerical simulation. In Minnesota, lodgement tills of the Rainy lobe of the Late Wisconsinan glaciation exhibit significant changes in sedimentology between tills associated with the Last Glacial Maximum (LGM) and those deposited late during ice retreat. These changes include a small, but systematic increase in the intermediate size of clasts in the tills from the LGM to final ice retreat. Clast size in lodgement tills directly relates to the basal sliding velocity of ice. Small clasts drag on the bed and “lodge”, whereas large clasts simply plow into the basal sediment, but the stresses on them are too large for deposition. Therefore, we can use the size of clasts in lodgement tills to estimate sliding velocity at various times in a glacial advance. This investigation uses field-based measurements of intermediate clast size in lodgement tills, along with the analyses of Weertman (1959, 1964), Iverson and Hooyer (2004), and Hooke (1977) to estimate sliding velocity. Clast size is determined photogrammetrically from field exposures along the path of the Rainy Lobe. Calculated sliding velocity is compared with independent calculation of the velocity based on mass balance profiles. Preconsolidation pressures of these lodgement tills and the shear strength of the subglacial sediment are also considered. These calculations provide an important calibration parameter for comparison to balance velocity calculations from mass balance studies of numerical simulation.